تعزيز مشاركة الطلاب في تعليم المفردات ببرنامج وورد وول القائم على الدماغ: دراسة تجريبية في المدرسة الإسلامية الابتدائية تانجيرانج - Elsy Nabila; Muhbib Muhbib; Wati Susilawati; Achmad Fudhaili (Al-Muyassar: Journal of Arabic Education, 2025)
This research aims to analyze the response and participation of fifth-grade students at Islamic Elementary School Mazraatul Ulum in Tangerang City in vocabulary learning using the brain-based Wordwall program. The research highlights the problem of low student participation, as their activities are limited to listening and writing down vocabulary without effective collaboration, which negatively affects their understanding and performance. The researchers used the quantitative descriptive approach using pre- and post-questionnaires to collect data. The research sample consisted of 36 students, with the data analyzed using a Likert scale. The results showed a significant improvement in the level of classroom interaction, as the average response increased from 73.81 in the pre-questionnaire to 80.61 in the post-questionnaire. This indicates an increase in student participation after using the program. The results confirmed the effectiveness of Wordwall in improving students' language proficiency and enthusiasm for learning. The research provides recommendations for using innovative teaching methods to enhance the quality of education and classroom interaction, which contributes to solving the challenges of vocabulary learning more effectively.